(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This study examined feminism as an intellectual and a socio-political movement that leads to gender equality and social change in general. It discussed how feminist thought has been transformed through the course of feminist history through various waves, emphasizing how the focus has moved in subsequent decades on legal and political rights to contemporary interactions with identity, representation, and intersectionality. The study has described key feminist theoretical schools of thought such as liberal, radical, Marxist, psychoanalytic, post structural and intersectional feminism and how they contribute towards the concept of gendered power relations. The study also appraised law, education, and employment-based feminism interventions by focusing on the initiatives to eliminate institutional biases, embrace inclusivity, and champion substantive equality. Through intersectionality and valuing the role of feminism in cultural and political change, the study highlighted the relevance of feminism as a process of change redefining social norms, structures, and discourses of justice.